A state-of-the-art review of functional magnetic resonance imaging technique integrated with advanced statistical modeling and machine learning for primary headache diagnosis - Li, Ming-Lin; Zhang, Fei; Chen, Yi-Yang; Luo, Han-Yong; Quan, Zi-Wei; Wang, Yi-Fei; Huang, Le-Tian; Wang, Jia-He (Frontiers in Human Neuroscience, 2023)
Primary headache is a very common and burdensome functional headache worldwide, which can be classified as migraine, tension-type headache (TTH), trigeminal autonomic cephalalgia (TAC), and other primary headaches. Managing and treating these different categories require distinct approaches, and accurate diagnosis is crucial. Functional magnetic resonance imaging (fMRI) has become a research hotspot to explore primary headache. By examining the interrelationships between activated brain regions and improving temporal and spatial resolution, fMRI can distinguish between primary headaches and their subtypes. Currently the most commonly used is the cortical brain mapping technique, which is based on blood oxygen level-dependent functional magnetic resonance imaging (BOLD-fMRI). This review sheds light on the state-of-the-art advancements in data analysis based on fMRI technology for primary headaches along with their subtypes. It encompasses not only the conventional analysis methodologies employed to unravel pathophysiological mechanisms, but also deep-learning approaches that integrate these techniques with advanced statistical modeling and machine learning. The aim is to highlight cutting-edge fMRI technologies and provide new insights into the diagnosis of primary headaches.Primary headaches, which do not stem from any underlying disease or secondary cause, are classified into four main categories according to the International Classification of Headache Disorders (ICHD-3) (2018): migraine, tension-type headache (TTH), trigeminal autonomic cephalalgia (TAC), and other primary headaches. Recent research shows that worldwide, around 52.0% (95% CI: 48.9-55.4) of people are affected by active headache disorder (Stovner et al., 2022), while findings from the 2019 Global Burden of Disease (GBD) study report a prevalence of 35.0% (32.3-37.7) for primary headaches (Steiner et al., 2020). Furthermore, a comprehensive review of the prevalence of primary headaches in child and adolescent was shown to be 62% (53-70) (Onofri et al., 2023). Primary headaches, chiefly TTH and migraines, have prevalences of 26.0% (22.7-29.5) and 14.0% (12.9-15.2), respectively (Stovner et al., 2022). TACs alongside other primary headaches are relatively rare, with incidence rates of about 0.05-0.